Overview of Commercially Available PCR Assays for the Detection of Aspergillus spp. DNA in Patient Samples - Rath, Peter-Michael; Steinmann, Joerg (Frontiers in Microbiology, 2018)
Invasive aspergillosis (IA) is a live-threatening infection in immunocompromised patients. Early diagnosis is essential to improve survival. Since the nineties attempts for PCR-based diagnosis of IA were made. Progress in the standardization of methods enabled the development of commercially available Aspergillus PCR assays in the last few years. Up to now, the clinical value of only a few commercial assays was investigated more extensively in large cohort studies. Most often, respiratory secretions such as bronchoalveolar lavage were investigated, but some studies also included serum samples from high-risk patients. The data indicate that Aspergillus PCR, most likely in combination with antigen detection, has the potential for early and reliable diagnosis of IA including azole resistance markers. With the broad implementation of this technique in routine diagnosis and incorporation into patient care pathways it might be expected that an improvement in management of IA and subsequently patient outcome can take place.